IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) UNTUK MENINGKATKAN TINGKAT KEAKTIFAN DAN PRESTASI BELAJAR MATA PELAJARAN SEJARAH - Irwan Abbas; Mohamad Naim (Metafora: Education, Social Sciences and Humanities Journal, 2020)
The aims to be achieved in this research are, first, to assess whether the application of cooperative learning type STAD can increase the rate of liveliness learn on the subjects of history. Second,  to assessing whether the application of cooperative learning type STAD able to increase learning achievements on the subjects of history. The design of this study was with the Control Group Pre-Test and Post Test design. The results of the analysis of the data can be inferred: 1 ) the application of type STAD of cooperative learning can increase the rate of liveliness to study for students on the subjects of history,  koofesien relative effectiveness of 7,69 %. So if a student receives a grade activeness 66 in a conventional classroom, the liveliness of students in the classroom with using the cooperative learning type STAD methods will rise to 66 + ( 7,69 % x 66 ) that is equal to  71,07;  2 ) the application of learning cooperative type STAD able to increase learning achievements on the subjects of history, koofesien relative effectiveness of 7.4 %. So if a student gets the value of 66 in the class conventional, the classroom using cooperative learning type STAD  will increase to 66 + (7.04% x 66) that is equal to 70.65.